2010
DOI: 10.4028/www.scientific.net/amr.123-125.363
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Tissue Adhesive from Rice Starch Nanocomposites

Abstract: The objective of this work is make tissue adhesives agent from Thai rice starch, then test the final products for scientific and medical properties following the laws of Thai health ministry, to demonstrate that this product can be used safely, as same as the standard product. The principal raw material is pharmaceutical grade, Thai rice starch powder. The additives are hydroxyapatite (HA) nanopowder, carboxymethylcellulose, lactic acid, gelatin, polyvinylalcohol and glycerol. All materials will be mixed in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…hydroxyapatite until homogenization and the prepared suspension was subsequently heated at 60°C for 48h. Porous materials were obtained by this method, with interconnected pores and pore dimensions smaller than 1µm 109 . For scaffolds development, after the preparation of polymeric gel, 20-50%wt.…”
Section: Mixing and Heatingmentioning
confidence: 99%
“…hydroxyapatite until homogenization and the prepared suspension was subsequently heated at 60°C for 48h. Porous materials were obtained by this method, with interconnected pores and pore dimensions smaller than 1µm 109 . For scaffolds development, after the preparation of polymeric gel, 20-50%wt.…”
Section: Mixing and Heatingmentioning
confidence: 99%
“…Natural Fibrin glue [24] Fibrous protein tissue adhesive from human blood plasma, which mimics the physiological coagulation cascade and polymerizes to form blood clots Rice starch [29] Rice starch-based bioadhesives were prepared by dissolving the material in water at 60 8C. Bioadhesion was tested for topical use Collagen [30] Collagen-based adhesives are mentioned as a new class of tissue glues Gelatin [31] Gelatin-based bioadhesives crosslinked with formaldehyde and/or glutaraldehyde were examined for cytotoxicity, flexibility, and bonding strength Chitosan [32,33] Chitosan nanoparticle bioadhesives were prepared and evaluated for adhesion, swelling, drug delivery, entrapment efficiency, and loading capacity Pectin [34] Pectin-based bioadhesives were prepared and tested for bioadhesion, swelling, and erosion Dextran [32] Dextran was used as the second component of a two-component bioadhesive system as a bone adhesive.…”
Section: Polymer Type Materials Descriptionmentioning
confidence: 99%
“…Hardness, compressibility, adhesion, cohesion, and rheological properties of PEG-based bioadhesives were examined. [29] They also prepared gelatin/nanocarbon nanocomposites and showed that with the addition of 0.3 wt% carbon nanopowder, improvement to the maximum bonding strength of this adhesive to porcine muscle tissue was noted. They investigated the adhesive properties of the final product and concluded that the nanocomposite bioadhesive had a high water resistance (i.e., the bioadhesive dissolved only after 7 d) which could be useful in the human body.…”
Section: Polymer Type Materials Descriptionmentioning
confidence: 99%
See 2 more Smart Citations